Karakterisasi Fe₂O₃ Hasil Sintesis Hijau Menggunakan Ekstrak Buah Dengen (Dillenia serrata): Characterization of Fe₂O₃ from Green Synthesis Using Dengen Fruit Extract (Dillenia serrata) - Nurmalasari; Nurhalima; Suaedi; Bakri, Suriyanto; Putri, Syukrika; Prayitna, Yusri (Journal of Engineering Science and Technology Applications, 2024)
Fe₂O₃ has many functions, including as a pigment and as a semi-conductor material. The use of this material depends on its characteristics. In this study, the characterization of Fe₂O₃ nanoparticles produced from green synthesis was carried out. Dengen fruit extract was used as a chelating agent with iron sand raw material from the Pajallesang River, Palopo City. The synthesis was carried out using the sol-gel method at pH 4.7. The gel sample was calcined at temperatures of 600°C, 700°C, and 800°C, after which it was characterized using XRD and XRF. The average crystallite size of Fe₂O₃ particles in iron sand and after being synthesized at temperatures of 600°C, 700°C, and 800°C were respectively 40.09 nm, 36.67 nm, 31.46 nm, and 69.04 nm. The increase in calcination temperature affects the Fe₂O₃ content, where the higher the temperature used, the lower the Fe₂O₃ content obtained. The Fe₂O₃ content in iron sand and after synthesis at temperatures of 600°C, 700°C, and 800°C were respectively 70.4%, 91.04%, 90.01%, and 88.82%